2020
DOI: 10.1177/1071100720964805
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Partial Plantar Fasciotomy via 2 Medial Portals vs Mini-Open Procedure for Refractory Plantar Fasciitis

Abstract: Background: The treatment of plantar fasciitis may require surgical intervention in patients with ineffective response to conservative treatment. There is a lack of evidence regarding the differences in clinical outcomes between the endoscopic and the mini-open procedures. The purpose of this study was to compare the clinical outcomes of the endoscopic partial plantar fasciotomy via 2 medial portals with mini-open partial plantar fasciotomy for treating refractory plantar fasciitis. Methods: A retrospective an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
(30 reference statements)
0
5
0
Order By: Relevance
“… 24 Considering this, the partial release of the plantar fascia attached to the calcaneal spur may be associated with pain alleviation. The pain resolution using endoscopic PFR without CSR 2 , 3 , 6 , 12 , 13 , 16 , 29 , 34 - 36 can be explained by a similar mechanism described above. Because of the PFR, the plantar fascia was released from the tensile loads, and the calcaneal spur avoided stresses from the plantar fascia.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“… 24 Considering this, the partial release of the plantar fascia attached to the calcaneal spur may be associated with pain alleviation. The pain resolution using endoscopic PFR without CSR 2 , 3 , 6 , 12 , 13 , 16 , 29 , 34 - 36 can be explained by a similar mechanism described above. Because of the PFR, the plantar fascia was released from the tensile loads, and the calcaneal spur avoided stresses from the plantar fascia.…”
Section: Discussionmentioning
confidence: 64%
“… 17 Endoscopic procedures for plantar fasciitis include PFR without calcaneal spur resection (CSR) and PFR with CSR. 2 , 3 , 5 , 6 , 8 , 11 - 13 , 16 , 17 , 20 , 29 , 34 - 37 Both procedures are reported to have good outcomes, suggesting that CSR might not be necessary for plantar fasciitis treatment.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of surgical procedures are available, all of which are designed to restore the normal anatomy and function of the foot and to eliminate pain. Several studies have shown that endoscopic surgery is more effective in the treatment of recalcitrant plantar fasciitis than open surgery, 7,13,24,25 therefore, the four‐step program of therapeutic surgeries carried out in this study was performed endoscopically to ensure its therapeutic efficacy. Several studies have found that endoscopic plantar fascia release is often satisfactory in the treatment of recalcitrant plantar fasciitis 10,26,27 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have found that endoscopic surgery is a safer and more effective treatment for Plantar fasciitis than open surgery, improving patient satisfaction earlier and returning to work more quickly. 13 But there is no “gold standard” to treat plantar fasciitis with a bone spur. In a meta‐analysis, due to the unstandardized nature of the surgical protocol, the available evidence does not demonstrate that endoscopic plantar fascia release is safe and effective for the treatment of plantar fasciitis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation